relationship between food security and urban violence A study in political geography (Journal of the College of Basic Education, 2022)
The size of the population is one of the most important elements of the consumption function, as the imbalance between consumption on the one hand and production and productive resources on the other hand can lead to faltering plans to achieve food security. The high percentage of urban growth in Iraq for the period 1947-2011 indicates that migration from rural to urban areas is still continuing due to faltering policies and agricultural development programs. This, in addition to the increased demand for food as a result of the change in the urban lifestyle, which increased the complexity of the problem of food security, and then the possibility of violence. Galtung has referred to three forms of violence as a result of hunger and poverty worldwide, including direct violence, indirect violence, and cultural violence. So the political and economic stability